Engine to wing structural design under critical loads caused by a propeller blade loss. (1st March 2018) - Armendáriz, I.; Olarrea, J.; García-Martínez, J.
Highlights: The article is able to present a pylon design that guarantees, with high level of confidence, no major hazard on the aircraft in a blade loss event. The effects of stiffness and strength changes on the mounting system are analyzed. The research covers different different parameters which can influence the phenomenon. This non-deterministic approach is able to achieve interesting outcomes. The model detects damage zones and failures and it is suitable to simulate the blade loss collapse sequence. Abstract: To support the propeller blade loss loads in a turboprop aircraft the engine mounting system has to be carefully designed. The joints have to withstand the flight loads, however, during the blade loss event they have to fail before the wing gets damaged. Using a FEM model and Monte Carlo simulation techniques the possible failure sequences for a broad spectrum of flight conditions have been obtained, including different propeller frequencies, blade loss sizes, angular positions where the blade is lost and also material properties. The structural model includes non-linear behavior, damages, and several types of failure together with stochastic variables which can incorporate parameter uncertainties. Finally, the pylon to wing support is designed to guarantee, with high level of confidence, no major hazard on the aircraft due to this dynamical phenomenon.